UIProtoCheck: A Checklist for Semantic Inspection of User Interface Prototypes - Macedo, Gretchen T. De; Fontão, Awdren; Gadelha, Bruno (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
User interface prototypes are widely used in software development to facilitate customer communication and explore ideas, especially in agile development teams. In addition, they often guide subsequent stages of the development process, such as coding, testing, and training. Given their effect on the software development cycle, UI prototypes must be included in quality assurance activities such as inspections. Existing UI inspection approaches aim to detect mainly usability problems and are designed to inspect implemented software. However, development costs could be reduced by early detection of design defects if prototypes were reviewed against software requirements before implementation. For this reason, we developed UIProtoCheck, a comprehensive checklist to inspect UI prototypes semantically according to the software requirements. To evaluate it, we conducted a study where 12 participants used our checklist to inspect three UI prototypes based on a given scenario. The results showed that teams with the best results achieved 67% effectiveness in identifying semantic errors previously included in the prototypes. These promising initial results indicate that UIProtoCheck can support the semantic inspection of UI prototypes.